51st AIAA/SAE/ASEE Joint Propulsion Conference 2015
DOI: 10.2514/6.2015-4188
|View full text |Cite
|
Sign up to set email alerts
|

Wave Rotor Combustor Turbine Model Development

Abstract: A quasi-one-dimensional code previously developed for axial wave rotor channels with on-rotor combustion is now extended for curved and canted channels to study the physics of a wave rotor combustor turbine. The unsteady gas dynamics in a wave rotor channel provides pressure exchange through travelling waves. Having on-rotor combustion will provide compression, combustion and expansion in a single device. Additionally, having a curved or a canted profile allows energy transfer from the gas to the blade due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…More recent studies further pursue gas turbine [15][16][17][18] and reciprocating engine [14,19,[19][20][21][22] enhancement. In addition, the field of applications has been extended through the application of wave rotors in refrigeration cycles [8,9,[23][24][25][26] and pressure-gain combustors [1,2,[27][28][29][30][31][32][33]. In comparison with the amount of numerical research on wave rotor design and performance, there are relatively few studies dedicated to the experimental characterisation of wave rotors.…”
Section: Literature Surveymentioning
confidence: 99%
“…More recent studies further pursue gas turbine [15][16][17][18] and reciprocating engine [14,19,[19][20][21][22] enhancement. In addition, the field of applications has been extended through the application of wave rotors in refrigeration cycles [8,9,[23][24][25][26] and pressure-gain combustors [1,2,[27][28][29][30][31][32][33]. In comparison with the amount of numerical research on wave rotor design and performance, there are relatively few studies dedicated to the experimental characterisation of wave rotors.…”
Section: Literature Surveymentioning
confidence: 99%
“…(8) and solved using the same numerical scheme as axial channels. The modified equations for a wave turbine were verified against numerical predictions from NASA GRC [29] for the specific case of an expansion wave originating at one end of a non-axial channel, traveling through the length of the channel and reflecting at the end wall [19]. The results confirmed that in a non-axial channel the arrival of the wave after reflection from the end wall is delayed, consistent with the increased length of travel for the wave.…”
Section: Numerical Integration Schemementioning
confidence: 62%
“…The wave rotor can also be designed as a reacting flow device, resulting in precompression, mechanically confined constant-volume combustion and expansion in a single device. Nalim and co-workers have studied internal combustion wave rotors extensively through both computational and experimental work [8,[15][16][17][18][19][20][21][22][23][24][25][26][27]. The previous experimental and numerical work on wave rotor development focused on characterizing the wave processes that result in pressure exchange and on internal combustion, and therefore mostly concentrated on axial channels.…”
mentioning
confidence: 99%
“…Combustion happens at a nearly constant-volume condition since both end of the channel are closed after the recharge phase. Therefore, combustion products are discharged through the opening of the seal plate to the manifold [66]. Unlike PDE and RDE, WRCs can operate at nearly stationary conditions (except for the combustion chambers) due to the considerable number of channels receiving and discharging continuously flow during the rotation.…”
Section: Wave Rotor Combustors (Wrc)mentioning
confidence: 99%